Respuesta :
x + y = 3
2 x - y = 6
--------------
We will use the substitution method:
1st equation: y = - x +3
2nd equation: 2 x - ( - x +3 ) = 6
2 x + x - 3 = 6
3 x = 9
x = 9 : 3
x = 3
Answer: The x-coordinate of the solution to this system of equation is 3.
2 x - y = 6
--------------
We will use the substitution method:
1st equation: y = - x +3
2nd equation: 2 x - ( - x +3 ) = 6
2 x + x - 3 = 6
3 x = 9
x = 9 : 3
x = 3
Answer: The x-coordinate of the solution to this system of equation is 3.
Answer: 3
Explanation: Don't have an explanation except for the fact that i got it right on my test
Can I PLEASE have brainliest?